The Danish secret to happy kids : how the Viking way of raising children makes them happier, healthier, and more independent - Russell, Helen, 1980- (Sourcebooks, 2024)
"What do Vikings know about raising children? Turns out, quite a bit. After a decade of living in Denmark, and raising her three kids there, Helen Russell noticed that Nordic kids (or mini-Vikings) are different from children raised in other parts of the world. They eat differently. They learn differently. They play, dress, and even sleep differently. They run, jump, climb, fall and get up again, out in nature, for hours a day. It's cold and wet and uncomfortable--often. But they cope. Even though the weather's terrible and it's dark October through March. And then they grow up to be some of the happiest adults on the planet. So her question was: how? In The Danish Secret to Happy Kids, Russell dives deep into the parenting culture of Denmark and the other Nordic nations, from parental leave policies to school structure to screen time, uncovering surprising strategies and customs that lead to largely happy, well-adjusted humans over the long term. This fascinating peek behind the cultural curtain allows readers to marvel over infants comfortably sleeping outside in chilly temperatures, school-age kids wielding axes in the woods, and teenagers spending a year or two at efterskole, a special boarding school designed to prepare adolescents for independent life in the real world--a concept that is beginning to be adopted in other nations. Refreshingly funny and unfailingly optimistic about the new generation of humans growing up in the world right now, The Danish Secret to Happy Kids is a heart-warming love letter to Russell's adopted homeland, a comforting armchair travel read, and proof that we could all use a bit more Viking in our everyday lives." --